PEMBERDAYAAN MASYARAKAT BERBASIS PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA KELOMPOK USAHA TANI PEMBIBITAN TANAMAN BUAH - Kusuma, Indra Cahya; Wuryanto, Listio (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2019)
Micro and Small Enterprises (MSE) engaged in agriculture, especially breeding / breeding of fruit trees in the City and District of Bogor, especially in the Nagrog Village, South Bogor District and Karacak Village, Leuwiliang District, are still relatively small. Breeding / nursery activities are generally carried out in groups and from generation to generation, with traditional management and simple seed breeding techniques. There are several obstacles faced by farmers, including; limited capital, lack of production facilities and infrastructure and not understanding Accounting, especially never registering and not knowing how to prepare financial statements. This activity aims to increase economic capacity through the preparation of simple financial reports for fruit nursery farmer groups. The method used is in the form of counseling, training, mentoring and strengthening with techniques for recording transactions into journals, calculating the cost of goods, income statement and statement of financial position / balance sheet. The results of the activity indicate a change in mindset and knowledge in accounting. The farmer group has been orderly recording and can calculate the profit or loss of fruit plant nursery business.